الأحاديث المردودة المشتملة على ثواب عظيم لعمل يسير في كتاب "المجروحين" للإمام ابن حبان: (Rejected Hadiths that Include Great Rewards for Simple Deeds in the Book ‘al-Majrūḥīn’ by al-Imam Ibn Hibbān) - محمد جهاد البنا; فتح الدين بيانوني; ليلي سوزانا شمسو (At-Tajdid - Intellectual Refereed Journal, 2024)
Abstract This article highlights the study of hadiths containing promises for huge rewards on light action that mentioned by Ibn Hibbān in his book of al- Majrūhīn. These hadiths according to Ibn Hibbān have been reported by weak narrators an had been ruled out as invalid or fabricated hadith. This article also aims to highlight the effort of Imam Ibn Hibbān in criticizing the text of hadith, as well as to emphasize the attention of hadith scholars in criticizing both; the chain of transmission and the text of hadith. Hence, it clearly shows that they did not limit their view in criticizing one without the other. The study also intends to indicate the extent to which the imam’s ruling align or differ from those of other imams in these hadiths. This article adopts inductive approach in collecting the rejected hadiths by Ibn Hibbān due to it contain on rewarding huge awards upon simple deeds, as well as practicing descriptive and analytical approach in studying the hadiths and explaining the scholars’ views. This study concludes that Imam Ibn Hibbān paid significant attention in criticizing the text of hadith, although his book is primarily focuses on the biography of weak narrators. Apparently, this demonstrates the dedication of hadith scholars in analyzing and evaluating the text of hadith. Keywords: Rejected Hadith, Criticism The Text of Hadith, Huge Reward, Ibn Hibbān, The Book of al-Majrūhīn. .